Tests in Russian as a Foreign Language in the European System of Testing. - Домнич, С. П.; Косьмина, В. Ю. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article deals with the organization of the test control of students who study Russian as a foreign language. The system of levels in RFL according to the all-European competences of mastering foreign language skills has been considered. Special attention is focused on a set of grammatical knowledge, skills, abilities which the student learning RFL for the achievement of an appropriate level of the communicative competence has to master